Pengaruh Kualitas Produk, Persepsi Harga, Dan Promosi Terhadap Keputusan Pembelian Produk Kecantikan - Putri, Ariesya Marsha; Soliha, Euis (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Researchers conducted research on Scarlett Whitening products with the aim of knowing the influence of product quality, price perception and promotion on purchasing decisions for Scarlett Whitening products in Pati. This research method used is descriptive, uses google form, and uses primary data. This research used Purposing Sampling samples used on 112 respondents. The results of the analysis using the validity test, reliability test, multiple linear regression analysis test, F test, coefficient of determination test (R2), and t test, using the SSPS version 25 application. The results of the study analysis that have been carried out show: a. product quality has a standardized coefficient (beta) of 0.344 and a significance of 0.000; b. price perception has a standardized coefficient (beta) of 0.371 and a significance of 0.000; c. promotion has a standardized coefficient (beta) of 0.222 and a significance of 0.005. In conclusion product quality, price perception and promotion show that these variables have a positive and significant influence on purchasing decisions for Scarlett Whitening beauty products in Pati.